Magnetic resonance imaging for assessing hamstring injuries: clinical benefits and pitfalls - a review of the current literature - Greenky, M.; Cohen, S. B. (Open Access Journal of Sports Medicine, 2017)
Hamstring injuries are common injuries in all levels of athletics. Hamstring injuries can cause prolonged absence from sports and have a notorious rate of reinjury. Magnetic resonance imaging (MRI) is being increasingly utilized following a hamstring injury. Physicians are being increasingly asked to utilize MRI to predict clinical outcomes, including time frame for return to play and risk of reinjury. In spite of numerous studies in this area, no clear consensus exists. The purpose of this paper is to summarize the literature and evidence regarding the role of MRI in treating hamstring injuries